The effects of CYP2C9 and VKORC1 gene polymorphisms on warfarin maintenance dose in Turkish cardiac patients - KARAALP, ATİLA; SÜSLEYİCİ, BELGİN (FUTURE MEDICINE LTD, 2020)
Aim: Our aim was to examine the effect of CYP2C9 and VKORC1 polymorphisms on warfarin dose requirements in Turkish patients. Materials & methods: 24 warfarin prescribed patients were included and analyzed for eight VKORC1 and 6 CYP2C9 polymorphisms in the study. Results: Patients with CYP2C9 *1/*1 and VKORC1 -1639 GG and GA genotypes required higher warfarin doses in comparison to wild type VKORC1 genotype. Patients with CYP2C9 *1/*3 and VKORC1 -1639 GG genotypes simultaneously, required the lowest dose of warfarin (4.64 mg/day). Patients with CYP2C9 *1/*1 and VKORC1 9041 AA genotype were found to require higher warfarin doses. Conclusion: Our results provide additional evidence to support the hypothesis that CYP2C9 *2, *3, VKORC1 9041 G > A polymorphisms explain considerable proportion of inter-individual variability in warfarin dose requirement.
Keywords: 9041 G > A; CYP2C9; pharmacogenetics; VKORC1; warfarin